Comparative and cladistic analyses of the species of the genus Pelodera Schneider, 1866 (Rhabditidae: Nematoda) belonging to the coarctata group - Mahboob, Mohammad; Jahan, Rehmat; Tahseen, Qudsia (European Journal of Taxonomy, 2023)
Three new species of the genus Pelodera Schneider, 1866 viz., P. indica sp. nov., P. adeeli sp. nov. and P. paratretzeli sp. nov. collected from dung beetles and P. cylindrica (Cobb, 1898) collected from soil samples, are described and illustrated. Pelodera indica sp. nov. is characterised by sexual dimorphism in anterior region, cupola-shaped tail with a spike; males having punctated, striated and lobed bursa with no genital papillae originating anterior to cloaca. Pelodera adeeli sp. nov. is characterised by coarsely annulated cuticle; relatively narrow stoma; tail conoid without spike; males with punctated, lobed bursa and nine pairs of genital papillae arranged in a 2/1+2+P+3+1 configuration. Pelodera paratretzeli sp. nov. is characterised by sexual dimorphism in anterior region, stoma wide with three well-developed metastegostomal denticles; tail cupola-shaped with a long spike; males having spicules fused distally up to 12–14% of spicule length; bursa peloderan, anteriorly closed and punctated with nine pairs of genital papillae arranged in a 3/2+P+3+1 configuration. Pelodera cylindrica is described with additional details. The comparative analysis as well as phylogenetic relationship of the species belonging to the coarctata group have been elaborated by incorporating scanning electron microscopic observations. Information on the biogeographical distribution has also been provided.